Catalytic synthesis of chalcone and flavanone using Zn-Al hydrotalcite adhere ionic liquid - Kunde, Lalita B.; Gade, Swapna M.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Catalysis Communications, 2009)
The Claisen-Schmidt condensation of 2'-hydroxy acetophenone and benzaldehyde to chalcone and flavanone show that calcined Zn-Al (6) hydrotalcite is active for this synthesis. Coating of ionic liquid `1-(tri-ethoxy-silyl-propyl)-3-methyl-imidazolium chloride' on Zn-Al hydrotalcites was accomplished employing incipient wetness process and on NaY, NaX, MK-5 and silica gel employing co-condensation methodology. Impregnated IL on calcined Zn-Al (6) catalysts were characterized by XRD, SEM, BET, (13)C and (27)Al NMR analysis and the activity of these catalysts were investigated for chalcone and flavanone synthesis. (27)Al CP MAS NMR technique was used to show that interaction of IL with hydrotalcite modifies the acid-base sites and is responsible for enhancement of catalyst activity. Several aromatic aldehydes were screened to assess the general applicability of the system. (c) 2009 Published by Elsevier B.V.
Keywords: (27)Al CP MAS NMR; chalcone; Claisen-Schmidt condensation; Flavanone; Ionic liquid; Zn-Al hydrotalcite